Mitos, cuentos y leyendas del Perú e Hispanoamérica - Garcia Valdieviezo, Rosita Fernanda (2019)
The present work of professional sufficiency is structured in three parts, which are related to each other, whose theme is the myth, story and legend of Peru and Latin America. In addition to two livelihoods, one pedagogical and another scientific._x000D_ Within the learning session the competence, capacities and indicators to be treated for said session are specified, as well as the parties with their respective activities to be developed. In the pedagogical support, everything corresponding to a learning session is specified, defining concepts such as: society, learning, education, skills, abilities, strategies, evaluation, etc. In addition to the learning theories that will serve for its execution._x000D_ In what corresponds to the theoretical support, this is focused on defining the conceptual part of a myth, story and legend, adding each of these concepts, strategies and examples so that it is easy to understand and understand for the students with whom they are going to to work.